pH-Sensitive Nanomedicine for Treating Gynaecological Cancers - Vishwanath Prasad Pramod; Purkayastha Kakali; Sharma Utkarsh; Barik Mayadhar (Journal of Women's Reproductive Health, 2020)
Emergence of various nanoscale drug carrier platforms as Drug Delivery Systems (DDS) has revolutionized the field of medicine.Nonetheless, theside-effects due to non-specific distribution of anticancer therapeutics in normal, healthy tissues remain to be a prime pitfall in curing cancers. Therefore, to achieve a better therapeutic efficacy, the use of a target-specific delivery, combined with a stimuli-responsive nanocarrier system, particularly pH-sensitive nanosystems offer an attractive strategy. Targeted drug delivery through pH-sensitive nanosystems offer the potential to enhance the therapeutic index of anticancer agents, either by increasing the drug concentration in tumor cells and/or by decreasing the exposure in normal host tissues. Therefore, nanoscale-based drug delivery through pH-sensitive nanosystems seem to be a boon for treating gynaecological cancers (as well as other cancers) without side-effects or with least harm to normal healthy tissues.
Keywords: Gynaecological Cancers